NUSTAR: NUclear STructure Astrophysics and Reactions at FAIR. (3rd July 2018) - Kalantar-Nayestanaki, Nasser; Bruce, Alison
Abstract : NUSTAR is a collaboration of more than 800 scientists from 180 institutes in 38 countries who will perform key measurements to investigate the structure, decay properties, and reactions of nuclei leading to an understanding of the origin of the elements in the universe. NUSTAR is organized in nine sub-collaborations that will undertake competing and complementary measurements of important observables. In alphabetical order, the nine sub-collaborations are: